2018
DOI: 10.1002/dev.21790
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent morphine exposure increases nociceptive behaviors in rat model of formalin test

Abstract: The number of adolescents who use illicit drugs has increased dramatically. Adolescence is a critical period for brain development and maturation. The importance of the study of pain perception and the possible mechanisms involved is crystal clear. Up until now, there has been no evidence regarding the long‐term effect of adolescence morphine administration on pain perception. The objective of the present study was to investigate long‐lasting effect of adolescent morphine exposure on pain perception as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…The results of our laboratory study also showed that pain‐related behaviors were higher in morphine‐treated adolescents compared with morphine‐treated adult animals. These results confirm the sensitivity of adolescence to morphine exposure compared to adulthood (Ghasemi, Pachenari, Semnanian, & Azizi, 2019). On the other hand, some studies have acknowledged that substance use during adolescence does not have long‐lasting effects on the expression of anxiety‐like behaviors in adulthood (Bortolato et al., 2014; Higuera‐Matas et al., 2009; Rubino et al., 2008).…”
Section: Discussionsupporting
confidence: 84%
“…The results of our laboratory study also showed that pain‐related behaviors were higher in morphine‐treated adolescents compared with morphine‐treated adult animals. These results confirm the sensitivity of adolescence to morphine exposure compared to adulthood (Ghasemi, Pachenari, Semnanian, & Azizi, 2019). On the other hand, some studies have acknowledged that substance use during adolescence does not have long‐lasting effects on the expression of anxiety‐like behaviors in adulthood (Bortolato et al., 2014; Higuera‐Matas et al., 2009; Rubino et al., 2008).…”
Section: Discussionsupporting
confidence: 84%
“…We also found in another study that the morphine administration during adolescence, rather than in adulthood, has a lasting effect on nociceptive behaviors. The adolescent morphine-treated animals exhibited a higher nociceptive score in all three phases of the formalin test compared to the adolescent saline-treated group (Ghasemi et al, 2019).…”
mentioning
confidence: 79%
“…Numerous studies have revealed the long-lasting effects of opioids, especially morphine exposure during adolescence, on various physiological functions, such as learning, memory, anxiety, and pain perception (Ghasemi et al, 2019;Khani et al, 2022aKhani et al, , 2022bKhani et al, , 2023Pachenari et al, 2018;Salmanzadeh et al, 2020Salmanzadeh et al, , 2021. A previous study from our laboratory demonstrated that adolescent morphine exposure (AME) influences pain behaviors in subsequent generations.…”
mentioning
confidence: 99%
“…Results from behavioral tests, related to reaction-time, 24 h and 25 days after administration of morphine to adolescent rats found a profound effect on motor impulsive behavior later in adulthood (Moazen et al, 2018). Regarding pharmacological effects of chronic morphine administration during adolescence, this treatment increased pain responsiveness, in the formalin test, in adult rats compared to controls (Ghasemi et al, 2018). Adolescent oxycodone exposure resulted in increased sensitivity to the rewarding effects of opioids in adult mice (Sanchez et al, 2016).…”
Section: Introductionmentioning
confidence: 91%